TEACHERS’ EFFORTS TO INCREASE STUDENT LEARNING MOTIVATION IN ENGLISH LEARNING - Ermita, Mira; Halimah (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
Motivation is an important factor in determining student success in the teaching and learning process. The purpose of this research is to analyze and determine the efforts made by teachers to increase students’ motivation to learn English. This research is done to find out teachers’ efforts to increase student learning motivation in English learning at The State Vocational Senior High School 3 Jambi City. This research focuses on teachers’ efforts to increase students’ motivation to learn English and to find out the obstacles students experience during English learning. The type of research used is field research using a qualitative approach with a descriptive study method. The primary data source in this research is the English teacher at The State Vocational High School 3 Jambi City. In comparison, the secondary data course in this research is class XI students at The State Vocational High School 3 Jambi City. The data collection instruments for this research use interview, observation, and documentation techniques, the data was analyzed through data reduction techniques, data presentation, and data verification. The results of this research conclude that the English teacher’s efforts to increase students’ learning motivation include learning methods used, giving assignments and assessments to students individually or in groups, giving praise, and giving punishment to students who do not complete their tasks.